2017
DOI: 10.1038/s41467-017-01793-w
|View full text |Cite
|
Sign up to set email alerts
|

3D genome of multiple myeloma reveals spatial genome disorganization associated with copy number variations

Abstract: The Hi-C method is widely used to study the functional roles of the three-dimensional (3D) architecture of genomes. Here, we integrate Hi-C, whole-genome sequencing (WGS) and RNA-seq to study the 3D genome architecture of multiple myeloma (MM) and how it associates with genomic variation and gene expression. Our results show that Hi-C interaction matrices are biased by copy number variations (CNVs) and can be used to detect CNVs. Also, combining Hi-C and WGS data can improve the detection of translocations. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
104
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(119 citation statements)
references
References 63 publications
11
104
0
1
Order By: Relevance
“…The 3D genome interaction maps of CD4 + and CD8 + T cells were next investigated (Figure S3C-I) (Li et al, 2018; Wu et al, 2017). The switch of A/B compartments from steady-state T cells to tolerant ones is shown for chromosome 10 in Figure S3G.…”
Section: Resultsmentioning
confidence: 99%
“…The 3D genome interaction maps of CD4 + and CD8 + T cells were next investigated (Figure S3C-I) (Li et al, 2018; Wu et al, 2017). The switch of A/B compartments from steady-state T cells to tolerant ones is shown for chromosome 10 in Figure S3G.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of this new knowledge, whole‐genome conformation studies have been used to decipher how development or developmental disease (Dixon et al , ; Fraser et al , ; Lupiáñez et al , ; Franke et al , ; Bonev et al , ), cancer (Flavahan et al , ; Taberlay et al , ; Hnisz et al , ; Wu et al , ), DNA damage (Aymard et al , ; Canela et al , ), cellular aging (Criscione et al , ), and genetic variation (Javierre et al , ) impact on the structure and function of the genome. Needless to say that the advent of 3C technology (see overview in Denker & de Laat, ) has also provided insights into the higher order genomic organization of bacteria (e.g., Le & Laub, ; Lioy et al , ), fungi (e.g., Mizuguchi et al , ; Kim et al , ; Tanizawa et al , ), nematodes (e.g., Crane et al , ), the Plasmodium falciparum parasite (Ay et al , ), and plants (e.g., Dong et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that chromatin contact map is highly influenced by the copy number events [15, 18]. Our analysis of Hi-C/3C-seq data demonstrated that interaction frequencies are positively correlated across cancer cell lines with the copy number tracks derived from the same cell line.…”
Section: Resultsmentioning
confidence: 51%
“…al. reported in multiple myeloma (MM) cells with whole/partial chromosomal gains/losses that copy number (CN)-amplified regions have higher interaction frequencies than CN-neutral (normal) regions [15]. They identified the TADs by insulation score method [6] using ICE-normalized interaction matrices [19] and found that the numbers of TADs increased by 25% and the average size of TADs decreases significantly compared to the normal B cells.…”
Section: Introductionmentioning
confidence: 99%